KATA KERJA BANTU MODAL SEBAGAI PENGUNGKAP MODALITAS BAHASA INGGRIS DAN PADANANNYA DALAM BAHASA INDONESIA - CAHYADI, TEGUH DWI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This study aims at describing three main concerns regarding the modal auxiliary verbs or modals as the English modality markers, namely, 1) the primary modals as modality markers, 2) the secondary modals as modality markers, and 3) the modals equivalent in Indonesian. The research data were taken from various sources of English grammar book, the book which relates to the research, and an English novel Twilight, with the data collection techniques were performed by using jot-down method. English grammar books used in this study are those written by Quirk et al., Frank Palmer, and Geoffrey Leech, while the Indonesian grammar book used is written by Hasan Alwi. The method used in this research is the descriptive-qualitative method, and the results of analysis are presented in descriptive-qualitative method. The results of the analysis indicated that the English modals express at least three kinds of modality, namely epistemic modality, deontic modality, and dynamic modality, and some degrees of modality namely possibility, probability, and necessity. The primary modal may expresses epistemic and deontic modality, can expresses the three kinds of modality, must expresses epistemic and deontic modality, will expresses epistemic and dynamic modality, and shall only expresses deontic modality. The secondary modals express the same kind of modality as the primary modals; might, could, should and ought to, and would are the secondary modals of may, can, must, dan will, with a list of possible intentions such as temporal reference, politeness or tentativeness, and an index of hypothesis. The modal equivalents in Indonesian show that those equivalents express the same kind and degree of modality as the modals express.